The effect of large-sided games with HIIT protocol on the anaerobic ability of student futsal players - I Dewa Made Aryananda Wijaya Kusuma; M. Fu’ad Fahrudin; Bayu Agung Pramono; Adi Pranoto; I Wayan Artanayasa; I Made Satyawan; Ketut Chandra Adinata Kusuma; Agus Himawan (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: This research investigates the impact of Large Sided Games training using a High-Intensity Interval Training.